Batik SMEs Digital Literacy Analysis on Digital Economic Readiness during the COVID-19 Pandemic - Wiwin Juliyanti; Yohanes Kristantio Wibowo (Integrated Journal of Business and Economics (IJBE), 2021)
This study aims to determine the effect of the level of digital literacy on readiness of community level for 2020 digital economy at Batik Small and Medium-sized Enterprises (SMEs). This study uses a quantitative approach with purposive sampling technique which determines 65 respondents in the Masaran, Sragen, Central Java Batik SMEs who have marketed the products through online using social media. The questionnaire was used to retrieve data. Descriptive analysis techniques and multiple linear regression were used to process the data. The results of the descriptive analysis show that the digital literacy level of the majority of Batik SMEs entrepreneurs is in the low category. The regression results indicate that digital literacy has a positive effect on the readiness of community level for 2020 digital economy with the level of gender, educational background, and internet networks as control variables, the higher digital literacy level owned by business people, the higher the community readiness to join the digital economy era which requires have the skills to use digital media also increase.